Inductive proximity sensor for metal detection - Roslee, Azrin Sazwani; Puspanathan, Jaysuman; Abdul Rahim, Ruzairi; Md. Yunus, Yusri; Ahmad, Anita; Ahmad, Nasarudin (Penerbit UTHM, 2016)
Proximity sensor is among the oldest electronic parts in automation history. The recent research and progress of inductive proximity wave (IPS) sensor has grown with various demands of the domain. The IPS sensors have several unique benefits, such as light weight, small size, and immune to adverse environmental conditions and have a high switching rate for rapid response specifications. Means that, with the ability to detect at close range, IPS is a very useful for precision measurement applications.